The development and ex vivo evaluation of a computer-aided quality control system for Barrett’s esophagus endoscopy - Jong, Martijn R.; Jaspers, Tim J. M.; van Eijck van Heslinga, Rixta A. H.; Jukema, Jelmer B.; Kusters, Carolus H. J.; Boers, Tim G. W.; Pouw, Roos E.; Duits, Lucas C.; de With, Peter H. N.; van der Sommen, Fons; de Groof, Albert Jeroen; Bergman, Jacques J. G. H. M.; on behalf of the BONS-AI Consortium (Endoscopy, 2025)
Background Timely detection of neoplasia in Barrett’s esophagus (BE) remains challenging. While computer-aided detection (CADe) systems have been developed to assist endoscopists, their effectiveness depends heavily on the quality of the endoscopic procedure. This study introduces a novel computer-aided quality (CAQ) system for BE, evaluating its stand-alone performance and integration with a CADe system.Method The CAQ system was developed using 7,463 images from 359 BE patients. It assesses objective quality parameters (e. g., blurriness, illumination) and subjective parameters (mucosal cleanliness, esophageal expansion) and can exclude low-quality images when integrated with a CADe system.To evaluate CAQ stand-alone performance, the Endoscopic Image Quality test set, consisting of 647 images from 51 BE patients across 8 hospitals, was labeled for objective and subjective quality. To assess the benefit of the CAQ system as a preprocessing filter of a CADe system, the Barrett CADe test set was developed. It consisted of 956 video frames from 62 neoplastic patients and 557 frames from 35 non-dysplastic patients, in 12 Barrett referral centers.Results As stand-alone tool, the CAQ system achieved Cohen’s Kappa scores of 0.73, 0.91, and 0.89 for objective quality, mucosal cleanliness, and esophageal expansion, comparable to inter-annotator scores of 0.73, 0.93, and 0.83. As preprocessing filter, the CAQ system improved CADe sensitivity from 82 % to 90 % and AUC from 87 % to 91 %, while maintaining specificity at 75 %.Conclusion This study presents the first CAQ system for automated quality control in BE. The system effectively distinguishes poorly from well-visualized mucosa and enhances neoplasia detection when integrated with CADe.